Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.11114/jets.v7i10.4323
|View full text |Cite
|
Sign up to set email alerts
|

The Investigation of Elite Athletes’ Psychological Resilience

Abstract: The performances of the athletes can change from competition to competition under the pressure of heavy exercise and success anxiety during the season. The help obtained from sports psychology in order to minimize these fluctuations in the performance of the athlete is an important component in increasing the psychological resilience of the athlete. The aim of this study is to examine the psychological resilience of elite athletes in terms of various variables. This research is a descriptive survey model study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 22 publications
1
7
1
2
Order By: Relevance
“…However, unlike our findings, some studies in the literature do not show a significant difference between the psychological resilience levels of individuals and their sports experience [63][64][65]. No significant difference was found between the students' goal commitment levels and the variable of doing sports or not.…”
Section: Discussioncontrasting
confidence: 99%
“…However, unlike our findings, some studies in the literature do not show a significant difference between the psychological resilience levels of individuals and their sports experience [63][64][65]. No significant difference was found between the students' goal commitment levels and the variable of doing sports or not.…”
Section: Discussioncontrasting
confidence: 99%
“…A descriptive screening model [49] investigated the psychological resilience levels of 147 elite athletes from football, basketball, volleyball, and gymnastics (79 males and 68 females aged 17-21) with the Psychological Resilience Scale. The cross-sectional correlational study [49] investigated resilience along with differences with gender, doping use, branch of sport, and doing self-talk before competition. Resilience was found to be at the moderate level and below the moderate level in different branches.…”
Section: Athlete Psychological Resiliencementioning
confidence: 99%
“…Resilience was found to be at the moderate level and below the moderate level in different branches. Özdemir found gender and sport branch differences with males and footballers being more resilient [49]. The psychological resilience process was presented with various stressors inside and outside of sport being dealt with by low or high resilience.…”
Section: Athlete Psychological Resiliencementioning
confidence: 99%
“…As a result of the literature review, despite the importance of psychological resilience and stress coping strategies in sport, few studies have examined these variables in athletes (Akman, 2019;Alıncak & Abakay, 2015;Arsan & Koruç, 2009;Arslan, 2016;Campen & Roberts, 2001;Codonhato et al, 2018;Erim & Küçük, 2017;Fletcher & Sarkar, 2012;Fountain, 2017;Hammermeister & Burton, 2004;Hosseini & Besharat, 2010;Karademir & Açak, 2019;Özdemir, 2019;Sarkar & Fletcher, 2014;Secades et al, 2016;Şahin & Güçlü, 2018;Tazegül, 2015;Yoo, 2001). Moreover, there has been little research on the martial arts (Greco, Fischetti, Cataldi & Latino, 2019;Litwic-Kaminska, 2013;Özdevecioğlu & Yalçın, 2010;Radochonski, Cynarski, Perenc & Siorek-Maslanka, 2011;Üstün, Gümüşgül, Demirel & Göral, 2014), especially about Karate (Boghrabadi, Arabameri & Sheikh, 2015;Turgut, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Codonhato et al (2018) also found differences in resilience between males and females. Some studies found that male participants' perception of psychological resilience was higher than for females (Fountain, 2017;Karademir & Açak, 2019;Ortega et al, 2017;Özdemir, 2019;Ramirez-Granizo et al, 2020). In the studies conducted by Bingöl and Bayansalduz (2016) and Hosseini and Besharat (2010), it was found that psychological resilience does not differ by gender.…”
mentioning
confidence: 97%